2020
DOI: 10.1002/ldr.3739
|View full text |Cite
|
Sign up to set email alerts
|

Win–win path for ecological restoration

Abstract: Ecosystem degradation is a major cause of poverty, and poverty further aggravates ecosystem degradation through a feedback known as the 'poverty trap' that can prevent sustainable socioeconomic development in ecologically fragile areas. However, most ecological restoration programmes have failed to improve the lives of residents of the targeted areas because planners failed to understand the driving forces behind the poverty trap. Finding the threshold conditions for the poverty trap, which represent the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 54 publications
0
29
0
1
Order By: Relevance
“…Farmers also highlighted poverty, low income from farming and lack of economic opportunities in general as factors that hinder restoration because the farmers are trapped in livelihood systems that drive forest degradation. While some studies show that forests can help address multidimensional poverty (DeFries et al, 2021; Miller et al, 2021), Cao et al (2021) note that where restoration policies do not address 'poverty traps' and urban demand for forest products from forest‐rich rural areas, such restoration efforts fail, as observed in northern Malawi (see Figure 3). Finally, we found that weak ecosystem governance structures militate against long‐term large scale forest restoration in local communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers also highlighted poverty, low income from farming and lack of economic opportunities in general as factors that hinder restoration because the farmers are trapped in livelihood systems that drive forest degradation. While some studies show that forests can help address multidimensional poverty (DeFries et al, 2021; Miller et al, 2021), Cao et al (2021) note that where restoration policies do not address 'poverty traps' and urban demand for forest products from forest‐rich rural areas, such restoration efforts fail, as observed in northern Malawi (see Figure 3). Finally, we found that weak ecosystem governance structures militate against long‐term large scale forest restoration in local communities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, since farmers cited poverty and low income from farming as one of the restoration challenges, our findings suggest that practising agroecology can potentially increase yield to address food needs, which would reduce dependence on livelihood systems that incentivize forest exploitation. If decent markets could be obtained for agroecological products, restoring agroecosystems/forests could in turn likely reduce poverty, all other things being equal, and break the 'poverty trap' (Cao et al, 2021). Policy initiatives that support agroecological markets, as described in Brazil (Valencia et al, 2019), could be pursued for these twin goals of viable rural livelihoods and forest restoration.…”
Section: Discussionmentioning
confidence: 99%
“…. 随着人口的增长与全球气候变化, 我国生态脆弱 区贫困化与环境保护的矛盾日益突出, 探索生态脆弱 区如何摆脱"贫困陷阱"、实现生态保护与社会经济可 持续发展, 是地球圈层人类环境和生态系统脆弱性和 恢复力等相关研究的关键科学问题之一 [63,64] . 一方面, 生态修复可以提升生态系统的水源涵养、水土保持和 生物多样性等功能, 为人类获取清洁水源、安全食品 以及多样的基因等提供了保障, 从而促进人类福祉的 提升 [65,66] .…”
Section: 发挥卫星遥感、无人机等新技术作用unclassified
“…However, inappropriate vegetation restoration could also be a threat to the poor farmers in marginal mountainous areas, where the slope cropland is an indispensable environmental resource for basic grain needs to survive the poors (Chen et al., 2015; Feng et al., 2005). Once faced with insufficient grain output and livelihood difficulties, poor farmers have to reclaim the restored slope cropland again (Cao et al., 2009a; Deng et al., 2016), thereby affecting the sustainability of vegetation restoration strategies and resulting in relapses into the vicious circle (Cao et al., 2021). Therefore, vegetation restoration programs need to be more elaborately designed when involved in the trade‐offs between green and grain.…”
Section: Introductionmentioning
confidence: 99%